2002
DOI: 10.1038/nn914
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes an efficient reference frame for vision?

Abstract: Vision requires a reference frame. To what extent does this reference frame depend on the structure of the visual input, rather than just on retinal landmarks? This question is particularly relevant to the perception of dynamic scenes, when keeping track of external motion relative to the retina is difficult. We tested human subjects' ability to discriminate the motion and temporal coherence of changing elements that were embedded in global patterns and whose perceptual organization was manipulated in a way th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Yet even inverted walkers are easier to detect with some mask phase offsets, although improvement is not as great as for upright walkers. This finding is consistent with the notion that some form information, albeit degraded, about inverted walkers is available to the visual system (e.g., see Tadin et al, 2002).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Yet even inverted walkers are easier to detect with some mask phase offsets, although improvement is not as great as for upright walkers. This finding is consistent with the notion that some form information, albeit degraded, about inverted walkers is available to the visual system (e.g., see Tadin et al, 2002).…”
Section: Resultssupporting
confidence: 90%
“…Form, however, also influences coherence judgments. Tadin, Lappin, Blake, and Grossman (2002) showed that coherence judgments were better when the local elements carrying the coherence signal were organized as a global moving form, such as upright biological motion, than when the local elements created inverted biological motion.…”
mentioning
confidence: 99%
“…Several previous observations might be reconciled within our proposed framework that vision of human and inanimate motions may exert differential top-down influences on automatic processes computing time. Thus, it is known that vision of upright point-light human movement enhances the detection of coherence of local dot motion above the level attained during vision of upside-down movement [36]. Vision of upright human movement also enhances the detection of rolling motion [37], and suppresses perceptual asynchronies in detecting motion onset and colour/form onset [38].…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this question is important not only for our understanding of motion perception, but also for elucidation of basic principles that underlie visual processing in general. While various types of visual cues can help guide integration and segregation of motion signals (Rivest & Cavanagh, 1996; Croner & Albright, 1997, 1999; Lorenceau & Alais, 2001; Tadin et al, 2002), the quality of sensory signals per se is an important factor determining the appropriate balance between integrating and differentiating processes (Faisal, Selen & Wolpert, 2008; Rubin, Van Hooser & Miller, 2015). Research by the author and other groups (Section 3.2) shows that the nature of spatial integration of motion adapts to visual conditions, with spatial summation giving way to spatial suppression as stimulus saliency increases.…”
Section: Introductionmentioning
confidence: 99%